Aegean Bronze Age rhyta - Koehl, Robert B. (Prehistory monographs, 2006)
List of Illustrations in the Text --List of Drawing Credits --List of Photographic Credits --1.Typology, History, and Development --Principle of Typology and Definition of Types --Definition of Classes and Their Nomenclature --Rhyton Groups: Typology of Rims, Handles, and Bases --Exclusions and Exceptions --Organization and Presentation --Aegean Rhyta --Type IV --Type Indeterminate --Foreign Imitations of Aegean Rhyta --2.Catalog --Aegean Rhyta --Type Indeterminate --Foreign Imitations of Aegean Rhyta --Representations of Aegean Rhyta --3.The Mechanical Functions of Aegean Rhyta --4.The Uses of Aegean Rhyta --Organization and Presentation.